Role of Oxidative Stress in Vascular Low-Grade Inflammation Initiation Due to Acute Salt Loading in Young Healthy Individuals - Ana Knezović; Nikolina Kolobarić; Ines Drenjančević; Zrinka Mihaljević; Petar Šušnjara; Ivana Jukić; Marko Stupin; Aleksandar Kibel; Saška Marczi; Martina Mihalj; Ana Stupin (MDPI AG, 2022)
This study aimed to investigate the effect of 7-day high-salt (HS) and the specific role of oxidative stress on vascular low-grade inflammation initiation in young salt-resistant healthy individuals. 30 young healthy individuals adhered to a 7-day low-salt (LS) diet (3.5 g salt/day), followed by a 7-day high-salt (HS) diet (~14.7 g salt/day) protocol. Pro- and anti-inflammatory cytokines, frequencies of peripheral blood Th17 and Treg cells, Th17/Treg ratio, enzymes SGK1, and p38/MAP kinase, as well as biomarkers of endothelial activation and oxidative stress, were measured before and after the 7-day HS diet protocol. Short-term HS diet significantly increased serum level of pro-inflammatory cytokines INF-γ, TNF-α, IL-9, and IL-17A levels, but also of anti-inflammatory cytokines IL-10 and TGF-β1. Relative amount of total SGK1 significantly increased, following the 7-day HS diet. Increased oxidative stress level, following HS diet, was negatively associated with the frequency of Treg cells. The increase in relative amount of total SGK1 in peripheral mononuclear cells following 7-day HS diet suggests lymphocyte (re)activation, in response to HS intake, resulting in enhanced production of pro-inflammatory (IL-17, INF-γ), but also anti-inflammatory cytokines (IL-10 and TGF-β1). Increased oxidative stress, due to HS loading, alters immune regulatory mechanisms, presumably via effects on Treg cells.